Peningkatan Pengetahuan Manfaat HKI bagi UMKM Produk Pertanian di Banguntapan Kabupaten Bantul - Kusumawardani, Mawar; Subarjo, Abdul Haris; Setiabudi, Dedet Hermawan; Ahmadi, Nurfi; Nugroho, Fajar; Santoso, Prasidananto Nur; Santoso, Djarot Wahju (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) entrepreneurs still focus on trading and forget the potential side of intellectual property rights, this is due to ignorance, ego, or closed nature of business actors about new ideas and entrepreneurs feel quickly satisfied with their achievements. In product marketing communications, one of the functions of intellectual property rights is as a means for cultivating a positive image in the minds of consumers, so this needs to be understood by business actors, because the benefits of intellectual property rights for products are one of the important points so that MSME agricultural products are always remembered by the public or consumers who have tried the product for a period of time and have added value from the product. In this community service activity, a presentation was carried out, and to measure quantitatively the increase in knowledge, a pretest and posttest were conducted. The results of the increase in knowledge were an increase of 39% from the posttest results for community service participants.